2003
DOI: 10.1634/theoncologist.8-4-381
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thrombosis in Cancer Patients: Insights from the FRONTLINE Survey

Abstract: Background. Venous thromboembolism (VTE) is a common complication in cancer patients and a significant cause of morbidity and mortality. However, little information is available on oncologists' perceptions of the risk of VTE and its management. The Fundamental Research in Oncology and Thrombosis (FRONTLINE) study is the first comprehensive global survey of thrombosis and cancer. The study was designed to collect data on the perceived risk and patterns of practice with regard to VTE in cancer patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
2
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 19 publications
3
125
2
10
Order By: Relevance
“…Consistent with previous studies, in our study we observed the highest VTE rates in patients with brain tumors (high grade glioma) [30]. However, we did not find higher MP levels in the subgroup of patients with brain tumors compared to other tumor entities.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, in our study we observed the highest VTE rates in patients with brain tumors (high grade glioma) [30]. However, we did not find higher MP levels in the subgroup of patients with brain tumors compared to other tumor entities.…”
Section: Discussionsupporting
confidence: 92%
“…It has been estimated that one in seven hospitalized cancer patients who succumb to their disease do so from pulmonary embolism [4]. Of these patients, 60% have localized cancer or limited metastatic disease, which would have allowed for longer survival in the absence of a fatal embolic event.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most serious complications posed by an implanted port system is the appearance of port-induced sepsis [13,14]. It is also known that an advanced degree of metastasis or malignant tumor with a high one-year mortality rate (e. g. pancreatic cancer) entails elevated thrombophilia [15,16], which can in turn increase the risk of catheter lumen occlusion. This retrospective study aims to evaluate correlations between underlying disease and port complications.…”
mentioning
confidence: 99%